Common variable immunodeficiency associated with microdeletion of chromosome 1q42.1‐q42.3 and inositol 1, 4, 5‐trisphosphate kinase B (ITPKB) deficiency. Issue 1 (22nd January 2016) - Louis, Ankmalika G; Yel, Leman; Cao, Jia N; Agrawal, Sudhanshu; Gupta, Sudhir
Abstract : Common variable immunodeficiency (CVID) is a heterogenous disorder characterized by hypogammaglobulinemia and impaired specific antibody response and increased susceptibility to infections, autoimmunity and malignancies. A number of gene mutations, including ICOS, TACI and BAFF‐R, and CD19, CD20, CD21, CD81, MSH5 and LRBA have been described; however, they account for approximately 20–25% of total cases of CVID. In this study, we report a patient with CVID with an intrinsic microdeletion of chromosome 1q42.1‐42.3, where gene for inositol 1, 3, 4, trisphosphate kinase β ( ITPKB ) is localized. ITPKB has an important role in the development, survival and function of B cells. In this subject, the expression of ITPKB mRNA as well as ITKPB protein was significantly reduced. The sequencing of ITPKB gene revealed three variants, two of them were missense variants and third was a synonymous variant; the significance of each of them in relation to CVID is discussed. This case suggests that a deficiency of ITPKB may have a role in CVID. Immunodeficiency: Diagnosing a damaging deletion: Genetic analysis of an infection‐prone patient reveals a gene that may contribute to a complex immune disorder. Estimates suggest that up to 1 in 25, 000 people worldwide are born with common variable immunodeficiency (CVID), a genetic disorder that can cripple patients' immune defenses. Many genes contribute to CVID, and a case report from Sudhir Gupta and colleagues at the University of California at Irvine describes a new potential culprit. After examining a young man with developmental disorders and a history of recurrent infections, the researchers detected a sizeable deletion in one chromosome. Their analysis of the deleted segment of the chromosome led them to the ITP3KB gene, which encodes a protein associated with T and B cell functions. The patient's IPT3KB contained several mutations; two of them resulted in deficient production of ITP3KB protein which may play a role in immune deficiency.